Gillnet fishing characteristics in Franciscana Management Areas - Gonçalves, Isabel; Carvalho, Camila Carvalho de; Dias, Liane Amaral; Bertozzi, Carolina Pacheco [UNESP]; Domit, Camila; Tullio, Juliana Di (Elsevier, 2022)
The main threat to franciscanas (Pontoporia blainvillei) is the incidental catches in gillnets. Given the variety of this fleet and the fishing communities in Brazil, the aim of this chapter is to characterize the social-economic, socioenvironment, and ethno-environment aspects of the gillnet activity in the Franciscana Management Areas (FMA) II and III. There are few legislations to protect endangered cetacean species in Brazil focused on the creation of fishing exclusion areas and reduction of fishing effort, however, these norms have not complied because they are generalist and unknown by many fishers. The gillnet fisheries are diverse, and their local specificities and social vulnerabilities must be considered when elaborating public policies and conservation actions.
Keywords: Bycatch; Conservation; Fishermen; Franciscana; Public policies; Qualitative data